2012
DOI: 10.1177/0954411912459421
|View full text |Cite
|
Sign up to set email alerts
|

Design of new generation femoral prostheses using functionally graded materials: A finite element analysis

Abstract: This study aimed to develop a three-dimensional finite element model of a functionally graded femoral prosthesis. The model consisted of a femoral prosthesis created from functionally graded materials (FGMs), cement, and femur. The hip prosthesis was composed of FGMs made of titanium alloy, chrome-cobalt, and hydroxyapatite at volume fraction gradient exponents of 0, 1, and 5, respectively. The stress was measured on the femoral prosthesis, cement, and femur. Stress on the neck of the femoral prosthesis was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…This stress concentration at the sharp corner was excessively high. As the stress at the smooth corner was equivalent to that previously reported under similar experimental conditions [29], the sharp corner possibly led to this high stress concentration. These results indicated that the neck of the fractured stem might be exposed to stress above the fatigue strength of Ti-6Al-4V.…”
Section: Discussionsupporting
confidence: 62%
“…This stress concentration at the sharp corner was excessively high. As the stress at the smooth corner was equivalent to that previously reported under similar experimental conditions [29], the sharp corner possibly led to this high stress concentration. These results indicated that the neck of the fractured stem might be exposed to stress above the fatigue strength of Ti-6Al-4V.…”
Section: Discussionsupporting
confidence: 62%
“…The locations of the applied forces are shown in Figure 2. The femur was fixed at the distal end of the knee joint (Figure 1) [30, 39]. The bone and the cement layer were bonded in the cemented prosthesis implantation [40].…”
Section: Methodsmentioning
confidence: 99%
“…They found that the FG prostheses preserved the host bone better than the prostheses with conventional materials owing to having more mechanical stimuli, more uniform interface shear stress, and smaller maximum interface stress. A three-dimensional FEA was conducted by Oshkour et al [30] to determine the performance of cemented FG prostheses with a longitudinal gradient direction during a gait. They found less stress in the FG prostheses and more stress develops in the bone and the cement.…”
Section: Introductionmentioning
confidence: 99%
“…FGBM is a nonhomogeneous biomaterial composed of bioceramic and biometal; its properties such as elasticity modulus, mass density, and thermal conductivity vary smoothly and continuously through the biomaterial. Due to the high applicability of FGBM composite biomaterials, a number of researches have been dedicated many times to the biomedical applications of FGBM composites [11][12][13][14][15][16]. In the case of dental implants, FGBM is usually considered to comprise a mixture of titanium and bioactive hydroxyapatite (HA) due to its biocompatibility, bioactivity, and structural resemblance to that of the organic part of the teeth and body bones.…”
Section: Introductionmentioning
confidence: 99%